Password Recovery Using Graphical Method - Kharudin, WM; Din, NFM; Jali, MZ (Springer-Verlag Berlin, 2024)
Authentication with images or better known as graphical password is gaining its recognition as an alternative method to authenticate users, for it is claimed that images or pictures are easier to use and remember. The same method can be applied to password recovery, with the purpose to ease the process of users in regaining their account in case of forgotten passwords. A total of 30 participants were asked to use a prototype implementation of graphical password recovery and provide feedbacks. The data gained were analyzed in terms of attempts, timing, pattern, and user feedback. Overall, it was found that participants had no problem in using graphical password recovery despite they were new to it. Most of them preferred the choice-based method, even though they agreed that it provided less security. Graphical recovery has potential to be used more widely in current technology, although more works need to be done to balance the issues of usability and security.